Influence Of Customer Orientation, Technology Orientation And Entrepreneurial Orientation On Product Innovation In MSMEs The Halal Food Sector In North Bekasi City - Siti Komariah; Eri Bukhari; Ratna Suminar S (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study analyzes the influence of technology orientation and customer orientation on the product innovation of Food Halal MSMEs in North of Bekasi. This research uses quantitative methods and statistical analysis tools in the form of smartpls 4.0. This study used a Food and Baverage Halal MSMEs in North of Bekasi for a unit analysis. Sampling technique in this research with insidental sampling as 83 MSMEs. The results of this study found that there was an influence of customer orientation on product innovation but the different result fot technology orientation and entrepreneurial orientation are not infulnce and siginicant on product innovation. This research focuses on the MSMEs in North of Bekasi. In addition, the focus of this research is on the Halal food. The novelty in this study is that apart from the object of research, it is also a research model that has never been studied before.